A new classification of diabetes mellitus – current approaches and challenges - Alicja Szatko; Katarzyna Mordarska; Joanna Pokrzywa; Małgorzata Godziejewska-Zawada (Wiedza Medyczna, 2020)
Diabetes is a chronic metabolic disorder with a rapidly growing incidence worldwide. It is currently classified into two main types, type 1 and type 2 diabetes, based on status of the autoantibodies directed at the β-cell. However, it does not reflect the complexity of diabetes and the broad spectrum of the clinical manifestations, particularly in type 2.In this review we present the evolution of the World Health Organization (WHO) classification of diabetes, with a focus on newly introduced categories – hybrid forms of diabetes and unclassified diabetes. We compare the WHO diabetes subgroups with the American Diabetes Association (ADA) approach to this issue. Since the current classification systems do not reflect all the factors leading to hyperglycaemia in type 2 diabetes, we present novel approach to phenotyping diabetes in adults based on six variables (age at diagnosis, body mass index [BMI], C-peptide based homeostasis model assessments of β-cell function and insulin resistance, haemoglobin A1c and glutamic acid decarboxylase antibodies [GADA] status) which allowed to distinguish five replicable groups of patients in Swedish cohort with different clinical presentations.The understanding heterogeneity of diabetes helps to classify the patients more adequately, but none of classifications is optimal. Including combination of genetic, metabolomic and clinical factors into classification schemas will pave the way towards personalized medicine in diabetes and will presumably result in more effective treatment of the patients.